The Performance of the Shofar: Musical Liturgical Practice in Contemporary Christian Worship - Septian Cipto Nugroho; Wadiyo Wadiyo; Syahrul Syah Sinaga; Maria Angelita Widna (Institut Seni Indonesia Yogyakarta, 2025)
This study addresses the need to enhance theological and musical literacy in contemporary Christian worship, where the Shofar is often used without a clear understanding of its sacred sound structure. The Shofar, rooted in Torah and Talmudic traditions, embodies symbolic and acoustic meanings that have been reinterpreted in Christian liturgical contexts. By examining this conceptual gap, the research positions the Shofar as a symbol of resurgent church music whose theological and musical depth has frequently been overlooked. Using a liturgical studies framework that integrates theology and musicology, this qualitative case study was conducted among pastors, worship leaders, musicians, and Shofar players across five charismatic and Pentecostal churches in Java, Indonesia. Data were collected through interviews, participant observation, and document analysis, and analyzed using content analysis and the Miles, Huberman, and Saldana interactive model. Findings indicate that most practitioners emphasize the Shofar’s symbolic and emotional appeal while neglecting its tonal codes: Tekiah, Shevarim, Teru’ah, and Tekiah Gedolah. The study concludes by emphasizing the importance of restoring interpretive depth and theological discernment through structured liturgical understanding, ensuring that sacred sound continues to serve as a coherent medium of worship, theology, and musical formation.